Reading Multimodal General Geography Textbook in Secondary School Classes - Gergely, Marianna (Revija za elementarno izobraževanje, 2024)
The discussion deals with the reading of multimodal texts by determining the student’s ability to interpret content, expressed pictorially and verbally, while simultaneously understanding information from both semiotic resources. When reading multimodal texts, the student usually focuses on the verbal resource, and the pictorial one is considered marginal. We conducted research to understand: the dynamic in students’ meaning extraction from the textbook; their ability to understand the text; their greater attention to one resource or to both resources. The research proves that these students comprehend the information by focusing on the text, while the pictorial is interpreted as an addition.